The implication of transformational Teaching on Education And Learning System Act No. 4 1950 - Zulkarnain Zulkarnain; Rabaah binti Abdullah (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The purpose of this paper is to study the implication of Act No. 4 of 1950 on Teaching Fundamentals of Elementary School, Middle School, and Higher Education and its implementation to history teachings. This act was the first national formal bill on education policies, passed under the government of Mr. Asaat, the state president of the Republic of Indonesia. Although the state president was the one that created this act, the implementation of the system was introduced to all the other states of the country. This practice was considered uncommon in the state administration of Indonesia. Act No. 4 of 1950 contains the elementary educational purposes to provide students with fundamental knowledge, skills, and wisdom to develop their talent and interest for elementary students. While intermediate education assists the students to prepare for higher education, as well as cultivating experts in various fields according to their talents and fulfilling what society demands. The curriculum in higher education was created to prepare the students to become the future leaders of the society and provide them with the knowledge to conserve and develop the science and livelihood of the society. Act No. 4 of 1950 also influenced how history education goes. History should be able to be implemented into a learning process that can elevate the knowledge and cultivate a sense of nationalism in the youth generation of Indonesia